Inheritance of molecular markers linked to vascular streak dieback disease resistance in hybrid progenies of cocoa (Theobroma Cacao L.) - Midhuna M.R (Department of Plant Biotechnology and Molecular Biology, College of Horticulture, 2019)
Theobroma cacao L. (also known as the chocolate tree) is a major cash crop and the costliest beverage crop. Andhra Pradesh is the leading cocoa producing state in India but Tamil Nadu ranks first with an area of 26,969 ha. Vascular Streak Dieback (VSD) caused by the fungus Ceratobasidium theobromae is a serious disease in cocoa. Since it is a vascular pathogen, chemicals have little effect on disease control. The most tenable and economic technique to tackle this disease is by evolving resistant materials. Kerala Agricultural University had initiated VSD resistant breeding since 1995. Seedlings from hybridization, exhibiting high levels of resistance were selected and field established. Nineteen hybrids, exhibiting resistance to VSD (after screening for a period of thirteen years), were selected for the present study. The progeny obtained from these hybrids by crossing it among themselves were used as plant materials for the study. Two thousand two hundred and thirty seven flowers were pollinated and seven pods were obtained. About two hundred and sixty nine seedlings were grown from the seven hybridized pods in which nursery screening for disease resistance was done. Inoculum was dispensed by keeping already infected seedlings around the experimental materials. High humidity was ensured by providing over head sprinkler system. Visual screening recorded one hundred and eighty seedlings as disease resistant, fourteen seedlings as partially resistant and seventy five seedlings as disease susceptible. Three ISSR markers (UBC 811, UBC 815 and UBC 857) and one SSR marker (mTcCIR42) linked with VSD resistance gene, identified and validated from the previous studies were used for screening of the one hundred and twenty seedlings out of which one hundred and six were resistant and fourteen were partially resistant. The polymorphic band of 950 bp, which was found to be linked with the gene conferring VSD resistance was recorded in seventy seven resistant seedlings and three partially resistant seedlings, when screened with the primer UBC 811. When screened with the primer UBC 815 (750 bp) and UBC 857 (450 bp), the polymorphic marker band which was found to be linked with VSD resistant gene from the previous studies, was present in only twenty five resistant and one partially resistant seedling and twenty one resistant and one partially resistant seedling respectively. When screened with SSR marker, the 200 bp marker band, which was tagged with the VSD resistant gene was detected in fourty six resistant and six partially resistant seedlings. The ISSR marker UBC 811 and SSR marker mTcCIR42 were found to be having comparatively good percentage of inheritance among the segregating progeny screened with a mean inheritance percentage of 71.70 per cent and 48.78 per cent respectively. Flanking sequences of the ISSR markers UBC 811, UBC 857 and SSR marker mTcCIR42 were extracted from the whole genome database of cocoa. The ORFs from the flanking sequences of UBC 811 were identified to be uncharacterized proteins by using BLASTp tool. One ORF from the upstream sequence of the UBC 857 had shown identity with beta tubulin chain. Analyzing the distance between the marker and the flanking region, it was deduced that UBC 857 is a part of beta tubulin gene. Two ORFs were identified from both the upstream and downstream flanking sequences of the SSR marker. Using BLASTp tool, it was analyzed that both the ORFs showed more than 97 per cent identity to beta tubulin gene. Analysing the spacing between the marker and the flanking sequences, it was deduced that both the ORFs are part of the same gene and the SSR marker mTcCIR42 lies within the beta tubulin gene. Tubulin beta chain belongs to the microtubular component of cytoskeletal elements which provides resistance by not allowing the fungi to penetrate the outer epidermal wall of the plants, hence protecting the plants from infection. The ISSR marker UBC 857 and the SSR marker mTcCIR42 are linked to the beta tubulin gene, which provides VSD resistance by giving resistance against penetration of the plant cell by the fungus. Nineteen seedlings were identified to be having three or more markers expressed. They can be planted in the field and can be further evaluated for yield and yield contributing characters. Sequence of the beta tubulin gene can be used for primer designing, which can be used for confirmation by screening in resistant genotypes of cocoa.